The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4018/978-1-5225-0726-0.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Collaboration Amongst Novice Design Students

Abstract: This chapter presents a case study of a large common first year unit/subject in a major Australian university. The unit introduces students to the theory and practice of design through a learning environment that is brief and intense; being delivered in block mode over just four days, and being free of other academic commitments. Students choose from one of two concurrent environments, either a camping field trip or an on-campus alternative, and work in mixed discipline groups of six to nine students, on two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For the purpose of this study, a risk is defined as any factor which creates uncertainty about the outcome and has the potential to have a negative impact on any given project (Aven & Renn, 2009). Crowther et al, (2017), Kiernan et al, (2017) and Tang & Hsiao, (2013) discovered similarities between risks identified in design education and general education. Kiernan et al, (2017) examined the collaboration between groups of first-year Bachelor students, Master's students, and professional designers with varying levels of experience.…”
Section: Risk In Collaborative Design Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of this study, a risk is defined as any factor which creates uncertainty about the outcome and has the potential to have a negative impact on any given project (Aven & Renn, 2009). Crowther et al, (2017), Kiernan et al, (2017) and Tang & Hsiao, (2013) discovered similarities between risks identified in design education and general education. Kiernan et al, (2017) examined the collaboration between groups of first-year Bachelor students, Master's students, and professional designers with varying levels of experience.…”
Section: Risk In Collaborative Design Educationmentioning
confidence: 99%
“…Furthermore, Kiernan suggests that a lack of experience may also contribute to the risk's occurrence. Crowther et al, (2017) agreed that communication was a key risk factor but argued that the lack of positive relationships posed greater risks to the project outcome. Crowther agrees with Johnson et al, (2007) by suggesting that a strong relationship is required to foster an environment that allows students to share information and express their opinions.…”
Section: Risk In Collaborative Design Educationmentioning
confidence: 99%